Advances in tracking small migratory birds: a technical review of light‐level geolocation. Issue 2 (27th May 2013) - Bridge, Eli S.; Kelly, Jeffrey F.; Contina, Andrea; Gabrielson, Richard M.; MacCurdy, Robert B.; Winkler, David W.
ABSTRACT Light‐level geolocation data loggers, or geologgers, have recently been miniaturized to the extent that they can be deployed on small songbirds, allowing us to determine many previously unknown migration routes, breeding locations, and wintering sites. Use of geologgers on small birds has great potential to help address major research and conservation questions, but the method is not without its shortcomings. Among these shortcomings are the need to recapture birds after they have carried a device throughout a migration cycle and the potential for the devices to affect survival and behavior. We examined return rates of birds with geologgers in published and unpublished studies and found no evidence of a general negative effect of geologgers on survival, although there were a few individual studies where such an effect was evident. From these same studies, we found that most currently used harness materials are equivalent in terms of failure rates, and the most reliable geologgers are those made by the British Antarctic Survey (although these were also the largest geologgers used in the studies we examined). With regard to analysis methods, we believe there is much room for improvement. Use of online archiving of both data and analysis parameters would greatly improve the repeatability and transparency of geologger research.